2020
DOI: 10.3390/coatings10121244
|View full text |Cite
|
Sign up to set email alerts
|

Reinforced Superhydrophobic Anti-Corrosion Epoxy Resin Coating by Fluorine–Silicon–Carbide Composites

Abstract: SiC was modified by fluorine-containing organic substance 1H,1H,2H,2H-trifluoro-noctyltriethoxysilane (FAS) to change its hydrophilicity from hydrophilic to superhydrophobic nanoparticles, and the optimum conditions for hydrophobicity were effectively explored. Then, different content of fluorine-modified SiC (F–SiC) nanoparticles were added to the epoxy resin (EP) matrix to prepare composite coating samples. The results showed that the surface of SiC was modified by FAS to show superhydrophobicity, and the di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
22
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 33 publications
(23 citation statements)
references
References 54 publications
0
22
0
1
Order By: Relevance
“…The high-resolution spectral analysis for the B element on the surface of modified BN (Figure b) shows that the B1s peak can be decomposed into two Gaussian curves, one of which is from the binding energy of the B–N bond of BN itself (190.4 eV); the other is from the binding energy of B–O brought by −OH after NaOH attack (190.9 eV). For high-resolution spectrum analysis in F-SiC (Figure c), the Si2s peak can be deconvolved into three Gaussian curves, corresponding to Si–O–Si (102.4 eV), Si–C (103.1 eV), and Si–O–C (104.4 eV) . Similarly, the B element (Figure d), N element (Figure e), and C element (Figure f) in BN@F-SiC were analyzed by high-resolution spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…The high-resolution spectral analysis for the B element on the surface of modified BN (Figure b) shows that the B1s peak can be decomposed into two Gaussian curves, one of which is from the binding energy of the B–N bond of BN itself (190.4 eV); the other is from the binding energy of B–O brought by −OH after NaOH attack (190.9 eV). For high-resolution spectrum analysis in F-SiC (Figure c), the Si2s peak can be deconvolved into three Gaussian curves, corresponding to Si–O–Si (102.4 eV), Si–C (103.1 eV), and Si–O–C (104.4 eV) . Similarly, the B element (Figure d), N element (Figure e), and C element (Figure f) in BN@F-SiC were analyzed by high-resolution spectroscopy.…”
Section: Resultsmentioning
confidence: 99%
“…Corrosion holes on coated steel substrates were also observed for coatings composed of a polymer-tryptamine conjugate after 6 h, [70] and for nanofibers composite coating after 9 h exposure to salt spray. [93] For anticorrosion thicker coatings (≈30-60 µm) [94][95][96][97] and/or with superhydrophobic property, [96,97] corrosion holes appeared later. Some thicker coatings reported in the literature displayed a better anticorrosion property, but did not possess the dual functionality of anticorrosion and antibiofouling.…”
Section: Resultsmentioning
confidence: 99%
“…In their experiments, the authors used ZnO nanoparticles and hydrophobic vapor-phase SiO 2 nanoparticles to build micro-/nano-structures that enhance the roughness of superhydrophobic surfaces, while 1H,1H,2H,2H-Perfluorodecyldichloromethylsilane (FAS) was used to modify the surface of the nanoparticles to present low surface energy. Zhang et al reported a method to modify the SiC surface from intrinsically hydrophilic to superhydrophobic nanoparticles using fluorinated organic substance FAS [ 40 ]. As shown in Figure 4 f, the alcohol hydroxyl group of the hydrolyzed FAS and the hydroxyl group on the SiC surface undergo a dehydration reaction to form Si-O-Si.…”
Section: Siliconesmentioning
confidence: 99%